Inclusion of Soluble Fiber During Gestation Regulates Gut Microbiota, Improves Bile Acid Homeostasis, and Enhances the Reproductive Performance of Sows - Wu, Xiaoyu; Yin, Shengnan; Cheng, Chuanshang; Xu, Chuanhui; Peng, Jian (Frontiers in Veterinary Science, 2021)
Interaction between the dietary fiber and the gut microbes can regulate host bile acid metabolism. This study sought to explore the effects of guar gum combined with pregelatinized waxy maize starch (GCW) in a gestation diet on reproductive performance, gut microbiota composition, and bile acid homeostasis of sows. A total of 61 large white sows were randomly grouped into the control (n=33) and 2% GCW (n=28) groups during gestation. GCW diet increased birth-weight of piglets, and decreased the percentage of intrauterine growth restriction (IUGR) piglets. In addition, dietary GCW reduced gut microbial diversity and modulated gut microbial composition in sows on day 109 of gestation. The relative abundance of bile salt hydrolase (BSH) gene-encoding bacteria, Lactobacillus and Bacteroides decreased after GCW administration, whereas no significant difference was observed in the fecal level of total glycine-conjugated and taurine-conjugated bile acids between the two groups. Dietary GCW increased the relative abundance of Ruminococcaceae (one of few taxa comprising 7α-dehydroxylating bacteria), which was associated with elevated fecal deoxycholic acid (DCA) in the GCW group. GCW administration lowered the concentrations of plasma total bile acid (TBA) and 7α-hydroxy-4-cholesten-3-one (C4) (reflecting lower hepatic bile acid synthesis) at day 90 and day 109 of gestation compared with the control diet. Furthermore, the levels of plasma glycoursodeoxycholic acid (GUDCA), tauroursodeoxycholic acid (TUDCA) and glycohyocholic acid (GHCA) were lower in the GCW group compared with the control group. Spearman correlation analysis showed alterations in the composition of the gut microbiota by GCW treatment was associated with improved bile acid homeostasis and reproductive performance of sows. In conclusion, GCW-induced improves bile acid homeostasis during gestation which may enhance reproductive performance of sows.